White Hat, Black Hat, Slouch Hat: Could Australia's Military Cyber Capability be Deployed Under Commonwealth Call-Out Powers?. (June 2023) - Walker-Munro, Brendan
In April 2016, then Prime Minister Malcolm Turnbull confirmed the existence of Australia's offensive cyber capability. Said to constitute both a coordinating Information Warfare Division inside the Australian Army as well as dedicated cyberoffensive capability inside the Australian Signals Directorate, the unveiling of this capability was a watershed in Australian defence policy. Yet whilst the literature has briefly examined whether Australia's cyberoffensive capability is congruous with international law, no such analysis under Australia's domestic laws has been undertaken. This paper seeks to partially address this gap in the research by focusing on whether the Australian Defence Force could legally launch cyberattacks against domestic targets under Commonwealth call-out powers.